The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ijer.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Disabled students in higher education: Discourses of disability and the negotiation of identity

Abstract: University is a critical arena for young disabled people in the construction of an adult identity and in obtaining higher level qualifications which have a major impact on future labour market opportunities. In Scotland, statistics show that there has been a steady increase in the proportion of students who are disabled. However, adopting the identity of a disabled person at university is far from straightforward, in part because of the conflicting discourses surrounding disability which are encountered. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 4 publications
0
84
0
11
Order By: Relevance
“…They also wanted to describe the nature of their impairment in different terms (Watson, 2002, page 514). Recent research also confirms disabled students' rejection of such disabled discourses (Evans, 2014) and, in some cases, adoption of a disabled identity at different times and for different purposes; such as to enable access to disability-related funding (Riddell & Weedon, 2013). …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…They also wanted to describe the nature of their impairment in different terms (Watson, 2002, page 514). Recent research also confirms disabled students' rejection of such disabled discourses (Evans, 2014) and, in some cases, adoption of a disabled identity at different times and for different purposes; such as to enable access to disability-related funding (Riddell & Weedon, 2013). …”
Section: Discussionmentioning
confidence: 75%
“…For those students with unseen impairments, a disclosure, once made, cannot be retracted and may subsequently impact on the rest of their university experience and, potentially, into the employment setting (e.g. Houghton, 2006;Riddell & Weedon, 2013;Stanley, Manthorpe & White, 2007). Disabled students can therefore face a difficult choice, particularly if the placement provider is considered a potential future employer.…”
Section: Discussionmentioning
confidence: 99%
“…This data is relevant sense for people with disabilities higher education is an opportunity, an experience of empowerment and improvement of their quality of life [3], [4]. Also, at present, different works justify the convenience of including people with disabilities in higher education, since they contribute to building a better university [5].…”
Section: Introductionmentioning
confidence: 82%
“…A pool of studies illustrate that the number of students with specific learning difficulties entering higher education has increased (Griffin & Pollak, 2009;Griffiths, 2012;Kunttu & Pesonen, 2013;Valle, Solis, Volpitta, & Connor, 2004).The latest statistics reveal that 5% of students in Finnish HE have a learning difficulty of which dyslexia has been notified as the most common condition (74%) among them (Kunttu & Pesonen, 2013). The Finnish statistics do not reveal the field of study these students have enrolled in but the recent study by Riddell and Weedon (2014) reported that HE students with a diagnosis of dyslexia most typically (17. 6%) studied creative arts and design, and only 3.5 % were enrolled in the field of education.…”
Section: Diversity Within the Teaching Workforcementioning
confidence: 99%